Competencies and Barriers to the Use of Nursing Informatics among Nurses in Primary, Secondary and Tertiary Healthcare Facilities in Nigeria - Olajubu, Aanuoluwapo Omobolanle; Irinoye, Omolola Oladunni; Olowokere, Adekemi Eunice (Journal of Health Informatics in Africa, 2014)
Background and Purpose: Nurses have always been at the forefront of patient’s care and are expected to provide safe and quality care that is moderated by technology to consumers of health care. To meet these expectations, nursing informatics competencies are critical and essential for nursing practice. This study explored nurses’ knowledge, perception of their competencies and the barriers to the use of nursing informatics at the three levels of care in a State in Nigeria. This was done with the purpose of collecting baseline data to inform intervention for knowledge update and enhanced use of nursing informatics in practice.Methods: Adopting a cross sectional survey design, data was collected from 350 nurses from 1 tertiary, 6 secondary and 30 primary health care facilities using multistage sampling technique from 6 towns that have at least two out of the three categories of health care facilities in the State,. Proportionate samples were drawn based on the population of nurses in the 3 categories of health facilities with 175 from tertiary, 115 from secondary, and 60 from primary health care facilities.Results: The result showed a fair knowledge of nursing informatics by 55.4% of the respondents. In each of the three levels of competency, respondents perceived themselves as ‘competent’ and ‘not competent’ based on their self assessment. ‘Limited access to computer’ was the most perceived barrier by 55% of respondents to the utilization of nursing informatics.Conclusions: The study concluded that the competency of nurses in nursing informatics is poor due to various perceived barriers.Keywords: Competencies Informatics Barriers Nurses Nigeria